SOSIALISASI UU NO. 1 TAHUN 2022 DAN PP NO. 35 TAHUN 2023 PENYUSUNAN QANUN PAJAK DAERAH DAN RETRIBUSI DAERAH DI NAGAN RAYA - Yasrizal, Yasrizal; Eko Wahyuningsih, Yayuk; Trisna, Nila; Ukhty, Nabila; Rosmiati Sani, Sri (Universitas Teuku Umar, 2024)
The significant changes in regulations related to local taxes and levies in Indonesia, especially stipulated in Law Number 1 of 2022 concerning Regional Taxes and Levies and Presidential Regulation Number 35 of 2023, have prompted the need for a new approach in managing Regional Original Income (PAD) across Indonesia. The impact of these changes includes the repeal of previous regulations such as Law Number 11 of 2020 concerning Job Creation and Law Number 23 of 2014 concerning Regional Government. An academic team from Teuku Umar University conducted a Focus Group Discussion (FGD) with the Nagan Raya District government to assess the potential and sources of revenue from local taxes and levies. The discussion results revealed that there are still many untapped potentials for local taxes and levies. Therefore, it is essential for local governments to collaborate with all relevant agencies to optimize revenue collection from local taxes and levies. Amid the context of decentralization in Indonesia, district governments like Nagan Raya are challenged to find new sources of revenue from local taxes and levies to strengthen their financial independence.